Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada J&T Ekspress Surakarta - Bartolomeus Herawan Mintardjo (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
J&T Ekspress is a company engaged in freight forwarding services that has been established since 2014, located at, Surakarta.Tjiptono (2007) revealed that service quality is an effort to fulfill consumer needs and desires as well as the accuracy of delivery in meeting consumer expectations. This study aims to analyze the effect of service quality consisting of reliability, assurance, tangibles, empathy, and responsiveness to customer satisfaction at J&T EKSPRESS Surakarta.The research method used is descriptive analysis method and multiple linear regression, using the simultaneous significance test (F-test) and partial test (T-test) and the coefficient of determination (R2) using the Statistical Program of Social Science (SPSS) software version. 22 for Windows. The sampling method is purposive sampling method and the sampling is 80 respondents.Simultaneous test results show that service quality (X) consists of reliability, assurance, physical evidence, empathy, and responsiveness. has a significant effect simultaneously on the customer satisfaction variable with a significance value (P value) of 0.000 <0.05. The partial test results show that only the responsiveness variable has a partial significant effect on the customer satisfaction variable with a significance number (P Value) of 0.002 <0.05.